Narrative identity and well-being in vulnerable youth (Research, Society and Development, 2021)
Narrative Psychology aroused from research about the role of language on construction of psychological subjectivity. Biographical narratives help people to make sense on his experiences with the world and on building his identity. The way people organize life events and signify them in a narrative is fundamental to the establishment of a balanced personality. In the present work, we study the narrative construction of identity in adolescents in vulnerability situation. We seek the production of autobiographical narratives in search of construction of resilience and well-being. This work was designed as a multiple case study. Three adolescents of both sexes, aged between 13 and 16 years, participated in the study. They had an individual interview with the application of the Life Narrative Elicitation Interview protocol. The narratives were analyzed using the Narrative Matrix, by Gonçalves, Henriques and collaborators. Well-being indicators were discussed with the Big Three proposed by McLean and collaborators. Life stories showed different ways of dealing with suffering and seeking to overcome the difficulties in life. Narrative construction of well-being in the midst of difficulties was verified from an intertwining of the three dimensions of structural organization, autobiographical reasoning and motivational and affective elements. A balance was observed between the narrative elements in order to build an organized story and a balanced personality.